Missense Pathogenic variants in KIF4A Affect Dental Morphogenesis Resulting in X-linked Taurodontism, Microdontia and Dens-Invaginatus - Gowans, Lord J.J.; Cameron-Christie, Sophia; Slayton, Rebecca L.; Busch, Tamara; Romero-Bustillos, Miguel; Eliason, Steven; Sweat, Mason; Sobreira, Nara; Yu, Wenjie; Kantaputra, Piranit N.; Wohler, Elizabeth; Adeyemo, Wasiu Lanre; et al. (Frontiers in Genetics, 2019)
The etiology of dental anomalies is multifactorial; and genetic and environmental factors that affect the dental lamina have been implicated. We investigated two families of European ancestry in which males were affected by taurodontism, microdontia and dens invaginatus. In both families, males were related to each other via unaffected females. A linkage analysis was conducted in the New Zealand family, followed by exome sequencing and focused analysis of the X-chromosome. In the US family, exome sequencing of the X-chromosome was followed by Sanger sequencing to conduct segregation analyses. We identified two independent missense variants in KIF4A that segregate in affected males and female carriers. The variant in a New Zealand family (p.Asp371His) predicts the substitution of a residue in the motor domain of the protein while the one in a US family (p.Arg771Lys) predicts the substitution of a residue in the domain that interacts with Protein Regulator of Cytokinesis 1 (PRC1). We demonstrated that the gene is expressed in the developing tooth bud during development, and that the p.Arg771Lys variant influences cell migration in an in vitro assay. These data implicate missense variations in KIF4A in a pathogenic mechanism that causes taurodontism, microdontia and dens invaginatus phenotypes.